2015
DOI: 10.7577/pp.954
|View full text |Cite
|
Sign up to set email alerts
|

Physician Satisfaction and Physician Well-Being: Should Anyone Care?

Abstract: We present a model of hypothesized relationships between physician satisfaction, physician well-being and the quality of care, in addition to a review of relevant literature. The model suggests that physicians who are stressed, burned out, depressed, and/or have poor self-care are more likely to be dissatisfied, and vice-versa. Both poor physician well-being and physician dissatisfaction are hypothesized to lead to diminished physician concentration, effort, empathy, and professionalism. This results in misdia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
1
26
0
3
Order By: Relevance
“…This approach makes sense, given that so many of the complaints of physicians, particularly in the US, are negative reactions to a perceived loss of autonomy due to external directives-clinical guidelines, performance standards, or burdensome paperwork, as noted by Casalino & Crosson (2015) in this special issue. In the Healthy Work Place study, investigators functioned like management consultants, suggesting options with some underlying evidence; but participating practitioners ultimately decided which elements they would incorporate in their own plans and took responsibility for implementation.…”
Section: The Healthy Workplace Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This approach makes sense, given that so many of the complaints of physicians, particularly in the US, are negative reactions to a perceived loss of autonomy due to external directives-clinical guidelines, performance standards, or burdensome paperwork, as noted by Casalino & Crosson (2015) in this special issue. In the Healthy Work Place study, investigators functioned like management consultants, suggesting options with some underlying evidence; but participating practitioners ultimately decided which elements they would incorporate in their own plans and took responsibility for implementation.…”
Section: The Healthy Workplace Studymentioning
confidence: 99%
“…Existing measures aimed at the clinic staff as well as the physicians should probably be the starting point for instrument development. Much of the instrumentation could include validated survey instruments such as the recent RAND/AMA study (Crosson and Casalino, 2015) but some primary scale development could be done. Physician surveys should use uniform wording for core clinical tasks, patient physician relationships, demographics, educational, and health history information.…”
Section: Cross National Comparative Studymentioning
confidence: 99%
“…Similarly, Prins et al (2010) found that doctors who are more engaged in their work are significantly less likely to make mistakes, while another study (Leiter, Harvie, & Frizzell, 1998) suggested that nurses with higher work engagement have safer patient outcomes. "Engagement" therefore may be a more useful construct than job satisfaction since the latter somewhat confounds satisfaction with one's professional career choice and satisfaction with one's organization or the quality of care it permits (Casalino & Crosson, 2015).…”
mentioning
confidence: 99%
“…In fact, dissatisfaction and burnout increases the likelihood that physicians will engage in unprofessional behaviors, be less empathetic, and make errors. 2 Given the negative effects of burnout on quality of care and access to care, we have no choice but to address this issue for our patients.…”
mentioning
confidence: 99%
“…1 Physician dissatisfaction, burnout, or any other term used for this phenomenon has been linked to increased job turnover and early career termination, reduced patient satisfaction, increased use of tests and specialist referrals, and higher rates of physician depression and suicide. 2,3 Burnout affects physicians at all career stages, including medical students and residents. Much of the recent attention in the medical and general press has focused on physicians in practice.…”
mentioning
confidence: 99%